Halogens and trace metal emissions from the ongoing 2008 summit eruption of Kilauea volcano, Hawaii - Mather, T; Witt, M; Pyle, D; Quayle, B; Aiuppa, A; Bagnato, E; Martin, R; Sims, K; Edmonds, M; Sutton, A; Ilyinskaya, E (2012)
Volcanic plume samples taken in 2008 and 2009 from the Halemàumàu eruption at Kīlauea provide new insights into Kīlauea's degassing behaviour. The Cl, F and S gas systematics are consistent with syn-eruptive East Rift Zone measurements suggesting that the new Halemàumàu activity is fed by a convecting magma reservoir shallower than the main summit storage area. Comparison with degassing models suggests that plume halogen and S composition is controlled by very shallow (<3m depth) decompression degassing and progressive loss of volatiles at the surface. Compared to most other global volcanoes, Kīlauea's gases are depleted in Cl with respect to S. Similarly, our Br/S and I/S ratio measurements in Halemàumàu's plume are lower than those measured at arc volcanoes, consistent with contributions from the subducting slab accounting for a significant proportion of the heavier halogens in arc emissions. Analyses of Hg in Halemàumàu's plume were inconclusive but suggest a flux of at least 0.6kgday -1 from this new vent, predominantly (>77%) as gaseous elemental mercury at the point of emission. Sulphate is an important aerosol component (modal particle diameter ∼0.44μm). Aerosol halide ion concentrations are low compared to other systems, consistent with the lower proportion of gaseous hydrogen halides. Plume concentrations of many metallic elements (Rb, Cs, Be, B, Cr, Ni, Cu, Mo, Cd, W, Re, Ge, As, In, Sn, Sb, Te, Tl, Pb, Mg, Sr, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Hf, Ta, Al, P, Ga, Th, U, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, Tm) are elevated above background air. There is considerable variability in metal to SO 2 ratios but our ratios (generally at the lower end of the range previously measured at Kīlauea) support assertions that Kīlauea's emissions are metal-poor compared to other volcanic settings. Our aerosol Re and Cd measurements are complementary to degassing trends observed in Hawaiian rock suites although measured aerosol metal/S ratios are about an order of magnitude lower than those calculated from degassing trends determined from glass chemistry. Plume enrichment factors with respect to Hawaiian lavas are in broad agreement with those from previous studies allowing similar element classification schemes to be followed (i.e., lithophile elements having lower volatility and chalcophile elements having higher volatility). The proportion of metal associated with the largest particle size mode collected (>2.5μm) and that bound to silicate is significantly higher for lithophiles than chalcophiles. Many metals show higher solubility in pH 7 buffer solution than deionised water suggesting that acidity is not the sole driver in terms of solubility. Nonetheless, many metals are largely water soluble when compared with the other sequential leachates suggesting that they are delivered to the environment in a bioavailable form. Preliminary analyses of environmental samples show that concentrations of metals are elevated in rainwater affected by the volcanic plume and even more so in fog. However, metal levels in grass samples showed no clear enrichment downwind of the active vents. © 2011 Elsevier Ltd.